Classification of Pelvic Floor Fistulas (‘Vesicovaginal/Rectovaginal’): A Review - Judith Goh; Sum Sum Lo; Hannah Krause (Reproductive Medicine, 2025)
Pelvic floor fistulas are abnormal communications between the lower urinary tract and/or anorectum and the female genital tract. Classification systems for female pelvic floor fistulas have existed for over 150 years. At present, there is no consensus on a classification system. Traditionally, classification systems were used for obstetric fistulas. Earlier classification systems were descriptive (small/large/simple/complex) to communicate clinical findings. More recently, classification systems, in particular the Goh and Waaldijk systems, have been tested to predict the outcome of surgical closure and the risk of post-fistula closure urinary incontinence. Conclusions: Features of the fistula may predict outcomes following fistula surgery but other patient features and surgical experience and skill also play a role in the results.